"Shopping around" for treatment is not a solution to cancer backlog. (10th October 2022) - Aggarwal, Ajay; Walter, Fiona M; Sullivan, Richard; van der Meulen, Jan
Abstract : Ajay Aggarwal and colleagues argue that relying on patient choice to cut waiting times is oversimplistic and likely to widen inequalities